2016
DOI: 10.2196/mhealth.6469
|View full text |Cite
|
Sign up to set email alerts
|

A Brief Tool to Assess Image-Based Dietary Records and Guide Nutrition Counselling Among Pregnant Women: An Evaluation

Abstract: BackgroundDietitians ideally should provide personally tailored nutrition advice to pregnant women. Provision is hampered by a lack of appropriate tools for nutrition assessment and counselling in practice settings. Smartphone technology, through the use of image-based dietary records, can address limitations of traditional methods of recording dietary intake. Feedback on these records can then be provided by the dietitian via smartphone. Efficacy and validity of these methods requires examination.ObjectiveThe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 39 publications
0
32
0
Order By: Relevance
“…These findings are in line with previous reviews that found most direct‐to‐consumer apps do not draw on BCTs (Abroms, Padmanabhan, Thaweethai, & Phillips, ; Breton et al, ; Chomutare, Fernandez‐Luque, Arsand, & Hartvigsen, ; Cowan et al, ; West et al, ). Further, despite evidence that pregnant women find using mHealth for receiving feedback on their nutrition behaviour acceptable (Ashman, Collins, Brown, Rae, & Rollo, ), no apps in this review incorporated this BCT.…”
Section: Discussionmentioning
confidence: 93%
“…These findings are in line with previous reviews that found most direct‐to‐consumer apps do not draw on BCTs (Abroms, Padmanabhan, Thaweethai, & Phillips, ; Breton et al, ; Chomutare, Fernandez‐Luque, Arsand, & Hartvigsen, ; Cowan et al, ; West et al, ). Further, despite evidence that pregnant women find using mHealth for receiving feedback on their nutrition behaviour acceptable (Ashman, Collins, Brown, Rae, & Rollo, ), no apps in this review incorporated this BCT.…”
Section: Discussionmentioning
confidence: 93%
“…The DietBytes method may have been particularly acceptable for this cohort of women of childbearing age, as 92% ( n = 23) of participants reported that they use their phones for taking, sending, and uploading photographs at the time of recruitment. Our previous study demonstrated that providing feedback on the image-based dietary records via the smartphone in combination with consultation with a dietitian was well-received by participants [ 38 ]. The majority of women in the current study ( n = 18, 72%) indicated they would use the DietBytes method again to obtain feedback from a dietitian, but interestingly, over half ( n = 16, 64%) would use it for their own feedback or tracking of their diet (i.e., self-monitoring).…”
Section: Discussionmentioning
confidence: 99%
“…Traditional methods of dietary assessment can be burdensome and resource intensive [ 34 ]. Results from the current study highlight that a rapid, non-invasive assessment of skin coloration, measured objectively using reflectance spectroscopy at three body sites may be sufficient to estimate overall diet quality and frequency and variety of usual dietary intake, particularly for fruit and vegetables.…”
Section: Discussionmentioning
confidence: 99%